2013
DOI: 10.5511/plantbiotechnology.13.0312a
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid lethality with programmed cell death results from reciprocal interspecific crosses between Nicotiana nudicaulis Watson and N. tabacum L.

Abstract: Hybrid seedlings from reciprocal interspecific crosses between Nicotiana nudicaulis and N. tabacum were not viable when cultured at 28°C; this an example of hybrid lethality. Characteristically, shoot apices and root tips of these hybrids began to brown immediately after germination at 28°C. However, hybrid seedlings did not exhibit any symptoms of lethality at 34°C, and their growth was normal at this higher temperature. When hybrid seedlings were cultured at 34°C and then transferred to 28°C, lethal symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…When N. nudicaulis Watson, belonging to the section Repandae [11] [15], is crossed with N. tabacum, hybrid seedlings show lethal symptoms [1] [16], which are controlled by the S subgenome of N. tabacum [17]. However, this hybrid lethality is different from that expressed in crosses between section Suaveolentes and N. tabacum, whose lethality is not related to the Q chromosome [17].…”
Section: Introductionmentioning
confidence: 72%
“…When N. nudicaulis Watson, belonging to the section Repandae [11] [15], is crossed with N. tabacum, hybrid seedlings show lethal symptoms [1] [16], which are controlled by the S subgenome of N. tabacum [17]. However, this hybrid lethality is different from that expressed in crosses between section Suaveolentes and N. tabacum, whose lethality is not related to the Q chromosome [17].…”
Section: Introductionmentioning
confidence: 72%
“…nudicaulis were transferred to flat-bottomed test tubes that contained 10 ml of 1/2 MS medium supplemented with 1% sucrose and 0.25% Gelrite, pH 5.8, and cultured at 28°C, 34°C, or 36°C. In a previous report (Liu et al 2013), the desired results were obtained in a cross of N. nudicaulis×N. tabacum at 34°C.…”
Section: Cultivation Of Hybrid Seedlingsmentioning
confidence: 96%
“…In reciprocal interspecific crosses between N. nudicaulis and N. tabacum, hybrid lethality was observed at 28°C, but not at 34°C (Yamada et al 1999;Liu et al 2013). In this study, we crossed N. nudicaulis with two progenitors of N. tabacum, N. sylvestris (SS) and N. tomentosiformis (TT), to reveal which subgenome of N. tabacum contains the genomic factors responsible for hybrid lethality in hybrids between N. nudicaulis and N. tabacum.…”
mentioning
confidence: 99%
“…In hybrid seedlings of N. nudicaulis × N. tabacum expressing hybrid lethality, features of apoptosis such as chromatin condensation, nuclear fragmentation, and fragmentation of DNA were evident [38].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kobori and Marubashi [37] concluded that the T subgenome of N. tabacum encodes the causative gene(s) for hybrid lethality in the cross N. repanda × N. tabacum . On the other hand, the S subgenome of N. tabacum is related to hybrid lethality at 28°C in hybrids between N. nudicaulis and N. tabacum [38] , [39] . In contrast to research on the subgenome controlling hybrid lethality in N. tabacum , no studies of the subgenome of wild species involved in hybrid lethality have been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%